Gangguan Sekresi dan Sensitivitas Insulin pada Remaja dengan Riwayat Keluarga Diabetes Melitus Tipe 2 - Ardika, Okta Besti; Larasati, TA; Suharmanto, Suharmanto; Kurniati, Intanri (CV. Jasa Sukses Abadi, 2024)
Type 2 diabetes mellitus (T2DM) is a metabolic disorder characterized by impaired insulin secretion or hyperglycemia due to the inability of pancreatic β-cells to compensate for increased glucose levels in the blood. The pathophysiology of T2DM may result from the interaction of environmental and genetic factors. A person who has a family history of T2DM will experience genetic mutations that cause impaired insulin secretion and sensitivity. The genetic inheritance of the child is based on the parent alleles of both parents including some genes that have mutations. There are three types of genetic inheritance mechanisms described by parent of origin effects (POE), namely genomic imprinting, mitochondrial inheritance, and maternal intrauterine effects. The mechanism of impaired insulin secretion and sensitivity in someone with a family history of T2DM during puberty, which is also triggered by stress and hormonal imbalance, results in insulin resistance, especially significant when entering adolescence and supported by a family history of T2DM. In children with a family history of T2DM, it was found that pancreatic β-cell compensation was 30% lower compared to children without a family history of T2DM.